A Li-based MOF-derived multifunctional PEO polymer solid-state electrolyte for lithium energy storage. (3rd February 2022) - Han, Xiang; Wu, Tiantian; Gu, Lanhui; Tian, Dan
Abstract : A Li-based MOF has been successfully synthesized and applied in a solid-state lithium energy storage system. The MOF filler is added into the PEO-LiTFSI electrolyte, which exhibits both the mechanical strength and the ionic conductivity increase. Abstract : A three-dimensional (3D) metal–organic framework containing Li-oxygen clusters, namely {[Li2 (IPA)]·DMF} n (1 ) (H2 IPA = isophthalic acid), has been constructed under solvothermal conditions. The Li-based MOF can be applied to lithium energy storage. For example, it shows good compatibility with a PEO (LiTFSI) solid-state polymer electrolyte (SSPE). The PEO (LiTFSI) with the MOF additive shows an ionic conductivity of 1.1 × 10 −5 S cm −1 at room temperature. The 1D rhombic channels should facilitate lithium ion transportation and provide fast lithium ion pathway. Having assembled the PEO-MOF SSPE in a Li/Li symmetric cell and cycled at a current density of 0.1 mA cm −2, the polarization voltage was below 0.1 V during a 100 h test. The PEO-MOF SSPE was also used in a LiFePO4 -Li full cell and a high specific capacity of 144 mA h g −1 was achieved.